PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI PADA PERUSAHAAN ASURANSI AJB BUMIPUTERA KC LHOKSEUMAWE DAN PT TASPEN KC LHOKSEUMAWE) - Mursidah, Mursidah; Khairina, Khairina (Jurnal Akuntansi dan Keuangan, 2018)
This study aimed to determine the effect of Good Corporate Governance on the Quality of Financial Statements. The data used in this study were primary data obtained by distributing questionnaires to all respondents. The sample in this study amounted to 30 respondents who were selected using the Census sampling method. The data analysis method used was a simple Linear Regression method with the help of SPSS 17. The results of the study showed that Good Corporate Governance had an effect on the Quality of Financial statements partially. It is known that Good Corporate Governance has a significant effect on the Quality of Financial Statements. In addition, the R2 test showed that the value of R Square was 0.192, which means that the magnitude influence of the independent variable on the dependent variable was 19.2% and the remaining 80.8% was influenced by other factors outside of this research models.